2021
DOI: 10.7759/cureus.19876
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Perinatal and Maternal Outcomes in Borderline Versus Normal Amniotic Fluid Index in a Tertiary Care Center in Odisha: An Observational Prospective Study

Abstract: BackgroundAmniotic fluid is a protective fluid in the amniotic sac of a gravid uterus that serves many crucial functions by becoming part of an indicator of a functioning fetoplacental unit during the intrauterine life of a fetus. The most commonly used method for measuring amniotic fluid is the amniotic fluid index (AFI). In this study, we aimed to investigate the perinatal and maternal outcomes in borderline AFI versus normal AFI. MethodologyThis observational prospective study included 200 pregnant women wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Vyas A in his study of 200 pregnant women calculated a mean age of 28.5 years, a finding similar to our study. 14 The mean age was 25.17 years in the study by Sadia S which was less than the mean age of our patients. 15 The majority of women in our study were multigravida (76.5% versus 23.5%).…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…Vyas A in his study of 200 pregnant women calculated a mean age of 28.5 years, a finding similar to our study. 14 The mean age was 25.17 years in the study by Sadia S which was less than the mean age of our patients. 15 The majority of women in our study were multigravida (76.5% versus 23.5%).…”
Section: Discussioncontrasting
confidence: 61%
“…21 Vyas A also observed a very high cesarean section rate (59% versus 35%) in the borderline AFI group which might be because cases of IUGR and abnormal Doppler studies were not excluded. 14 Meconium staining of amniotic fluid was observed in 10.5% (19/180) and 6.6% (24/360) cases of borderline and normal AFI respectively in our study(p=0.116). There is an increased risk of meconium staining of liquor in postdate pregnancy, pre-eclampsia, prolonged labour, prelabour rupture of membranes, fetal distress, and intrauterine growth restriction.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…A study conducted in India to assess the fetomaternal outcome in borderline AFI vs normal AFI reported that the number of caesarean sections was significantly higher in the borderline AFI group, which supports our findings. They also reported that the incidence of low APGAR score at 5 minutes, low birth weight, and NICU admission were significantly higher in the borderline AFI group than the controls (Vyas et al, 2021).…”
Section: Resultsmentioning
confidence: 92%